Can hydroxyurea serve as a free radical scavenger and reduce iron overload in β-thalassemia patients?. (1st September 2016) - Italia, Khushnooma; Chandrakala, S.; Ghosh, Kanjaksha; Colah, Roshan
Abstract: In this study, we hypothesize that hydroxyurea could provide an additional benefit as a free radical scavenger and/or iron chelator in β-thalassemia patients with iron overload. Twenty-one β-thalassemia intermedia patients who presented between 3 and 17 years but later required regular blood transfusions were enrolled for hydroxyurea therapy for a year. Fourteen patients responded to the therapy with hemoglobin levels maintained above 7.5 g/dl without transfusions. Hydroxyurea was discontinued after 6 months in seven patients who did not respond to the therapy and had to be continued on regular blood transfusions. We observed a statistically significant decrease in serum ferritin levels from 4194 ± 4850 ng/ml to 2129 ± 2380 ng/ml among the responders and from 2955 ± 2909 ng/ml to 2040 ± 2432 ng/ml among the non-responders and statistically significant decrease in labile iron pool from 18678.7 ± 10067.4 mean fluorescence intensity (MFI) to 14888.5 ± 5284.0 MFI among responders and from 17986.3 ± 9079.8 MFI to 15634.8 ± 8976.9 MFI among the non-responders after therapy. Phosphatidylserine externalization also showed a statistically significant decrease from 44.2 ± 22.2 MFI to 16.6 ± 6.7 MFI among the responders and from 46.9 ± 33.1 MFI to 39.8 ± 7.4 MFI among the non-responders along with a statistically significant decrease in the levels of reactive oxygen species from 72.8 ± 35.5 MFI to 29.0 ± 8.3 MFI among the responders and from 80.9 ± 41.4 MFI to 40.5 ± 15.8 MFI among the non-responders after therapy. A statistically significant increase in reduced glutathione levels was also observed from 430.8 ± 201.1 MFI to 715.5 ± 292.4 MFI among the responders and from 359.6 ± 165.6 MFI to 450.3 ± 279.5 MFI among the non-responders after therapy. This suggests the possible additional role of hydroxyurea as a free radical scavenger and/or iron chelator but requires a larger study for substantiation.